NORMAL-SENSE SHEAR ZONES IN THE CORE OF THE HIGHER HIMALAYAN CRYSTALLINES (BHUTAN HIMALAYA): EVIDENCE FOR EXTRUSION? - Carosi R.; Montomoli C.; Rubatto D.; Visonà D. (My University, 2006)
Recent fieldwork in western Bhutan, dedicated to unravelling the tectonic structure of the mid-crustal rocks, indicates a complex deformation pattern in the Greater Himalayan Slab (GHS). A system of normal shear zones, striking NE-SW and steeply to moderately dipping to the SE, has been recognized within this extruding slab or wedge of crystalline rocks. The zones are characterized by well developed shear-sense indicators pointing to a top-down-to-SE sense of shear. The main Barrovian metamorphic minerals are bent and stretched by extensional shear bands and associated deformation mechanisms indicate a range of brittle-ductile deformation conditions. Normal shear zones are concentrated in the middle-upper part of the GHS and indicate a thrust-transport-parallel lengthening of the core itself. Vorticity analysis highlights a non-coaxial flow with pure and simple shear acting together during deformation (mean vorticity number bracketed between 0.63 and 0.76). These data, when compared to available data near the tectonic boundaries of the GHS, indicate an increasing component of pure shear towards the interior of the GHS. The ages of zircon overgrowths and monazites from a slightly deformed granite, 20.5 ± 0.5 Ma, and a mylonitic granite deformed into the shear zones, 17.0 ± 0.2 Ma, bracket the age of shear zone formation at close to 17 Ma. According to our data, the normal shear zones could well accommodate the pure shear component of deformation localized in the inner part of the extruding wedge/slab and is compatible with a channel flow model. © The Geological Society of London 2006.